Home Sweet Home: plasmodium vivax-infected reticulocytes : the younger the better? - Thomson-Luque, Richard; Bautista, José M. (Frontiers in Cellular and Infection Microbiology, 2021)
After a century of constant failure to in vitro culture the most widespread human malaria parasite Plasmodium vivax, recent advances have highlighted the difficulties to provide this parasite with a healthy host cell to invade, develop and multiply under in vitro conditions. The actual level of understanding of the heterogeneous populations of cells, framed under the name ‘reticulocyte’ and, importantly, its adequate in vitro progression from very immature reticulocytes to erythrocytes, is far for complete. The volatility of its individual stability may suggest the reticulocyte as an delusory cell, particularly to be used for stable culture purposes. Yet, the recent relevance gained by specific subset of highly immature reticulocytes has brought some hope. Very immature reticulocytes are characterized by a peculiar membrane harboring a plethora of molecules potentially involved in P. vivax invasion and by an intracellular complexity dynamically changing upon its quick maturation into erythrocytes. We analyze the potentialities offered by this youngest reticulocyte subsets as an ideal in vitro host cell for P. vivax.
Gesehen am 27.05.2021